Bile acid–microbiota interactions in cardiometabolic diseases: mechanisms and emerging therapeutic approaches - Chen, Feiyu; Gong, Lihong (Frontiers in Microbiology, 2025)
The gut microbiota and bile acids co-regulate host metabolism through bidirectional interactions. This interaction critically influences the pathogenesis and progression of cardio-metabolic diseases (CMDs), which include diabetes, obesity, non-alcoholic fatty liver disease (NAFLD), and cardiovascular diseases. Growing evidence establishes bile acid metabolism as fundamental to the pathogenesis of CMDs. Bile acids activate both the nuclear receptor FXR and the membrane receptor TGR5, which in turn influence glucose and lipid metabolism, modulate inflammatory processes, and affect vascular functions. These signaling pathways collectively link metabolic and immune networks within the cardio-metabolic axis. This review provides an integrative overview of recent findings in bile acid signaling and its cross-talk with metabolic and immune pathways in CMDs. It critically evaluates disease mechanisms, discusses therapeutic candidates targeting bile acid pathways, and highlights future directions for the precise management of metabolic-immune disorders.